2017
DOI: 10.3390/socsci6030106
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Tourism Impact and Support Tourism Development in Terengganu, Malaysia

Abstract: (1) Background: Tourism is a prominent industry with the capability to generate income for developed as well as developing countries. However, studies are still lacking, particularly those specifically investigating the perception of local residents towards tourism. The perception of the locals is important, since it could determine the extent of their support for tourism development. In addition, previous research has found that male residents are more supportive towards tourism development. Therefore, this f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 51 publications
2
27
0
1
Order By: Relevance
“…Figure 2 shows the value for each path in a model. The R 2 for the entrepreneurial intention was 0.28 or 28%, which exceeds the substantial value of R 2 (0.26 or 26%) as suggested by Cohen (1988) and Afthanorhan et al (2017). As the researchers had predicted, the cooperative involvement construct has a positive effect on entrepreneurial intention (β = 0.463, p< 0.001), which supports the hypothesis in this research.…”
Section: Structural Modelsupporting
confidence: 82%
See 1 more Smart Citation
“…Figure 2 shows the value for each path in a model. The R 2 for the entrepreneurial intention was 0.28 or 28%, which exceeds the substantial value of R 2 (0.26 or 26%) as suggested by Cohen (1988) and Afthanorhan et al (2017). As the researchers had predicted, the cooperative involvement construct has a positive effect on entrepreneurial intention (β = 0.463, p< 0.001), which supports the hypothesis in this research.…”
Section: Structural Modelsupporting
confidence: 82%
“…Some of the newly observed variables were added in this construct to enhance its meaning. All the measurements of the observed variables for entrepreneurial intention used the ten points-Likert scale (Rahlin et al, 2019) ranging from Strongly Disagree (1) to Strongly Agree (10) at the end. Meanwhile, the measurement of observed variables for cooperative involvement constructs used the ten points-Likert scales ranging from Never Been Involved (1) to Frequently Involved (10) at the end.…”
Section: Variables and Measurementmentioning
confidence: 99%
“…Statistically significant differences were found between female and male respondents and their perceptions about general infrastructure and tourism potential, with female respondents being more positive ( Table 7). Perhaps this is because, in general, female residents are more attracted by the tourism sector than male residents, with tourism representing an alternative source of income to agriculture in rural areas [51,52]. However, no differences were found when analyzing the difference related to the level of education (p > 0.05).…”
Section: County Mean (Sd)mentioning
confidence: 96%
“…The socio-demographic characteristics influence the perception of rural residents towards tourism development and their support [23,51,52]. Previous studies suggested that the influence of socio-demographic characteristics may differ among communities due to the particularities of the regions (customs, beliefs, stage of tourism development etc.).…”
Section: Hypothesis 1 (H1): Tourism Destination Quality Is Perceived mentioning
confidence: 99%
“…The debate on the role of tourism in local development is ongoing and numerous studies have been carried out on this subject (Picornell 1993;UNWTO 1998;Hernán Muñoz and Lema 2001;Barbini 2002Barbini , 2008Mantero 2004;Vergara and de Souza 2005;Álvarez Sousa 2005;Wallingre 2007;Cañizares Ruiz 2008;Yildirim et al 2008;Álvarez Sousa and Rodríguez 2009; Massukado Nakatani and Gonçalves 2013; Pérez Víctor et al 2014;Horrach Estarellas 2014;Orgaz Agüera and Morales 2015;Muresan et al 2016;Pulido-Fernández and Parrilla González 2016;Afthanorhan et al 2017;Zhu et al 2017 among others).…”
Section: Introductionmentioning
confidence: 99%